Biogenic Synthesis of Silver Nanoparticles Using Phyllanthus emblica Fruit Extract and Its Inhibitory Action Against the Pathogen Acidovorax oryzae Strain RS-2 of Rice Bacterial Brown Stripe - Masum, Md. Mahidul Islam; Siddiqa, Mst. Mahfuja; Ali, Khattak Arif; Zhang, Yang; Abdallah, Yasmine; Ibrahim, Ezzeldin; Qiu, Wen; Yan, Chenqi; Li, Bin (Frontiers in Microbiology, 2019)
Biogenic synthesis of silver nanoparticles (AgNPs) using plants has become a promising substitute to the conventional chemical synthesis method. In this study, we report low-cost, green synthesis of AgNPs using fresh fruit extract of Phyllanthus emblica. The biosynthesized AgNPs was confirmed and characterized by analysis of spectroscopy profile of the UV-visible and Energy dispersive spectrophotometer, Fourier transform infrared, X- ray diffraction pattern, and electron microscopy images examination. UV-visible spectra showed a surface resonance peak of 430 nm corresponding to the formation of silver nanoparticles, and FTIR spectra confirmed the involvement of biological molecules in AgNPs synthesis. In spherical AgNPs, the particle size ranged from 19.8 to 92.8 nm and the average diameter was 39 nm. Synthesized nanoparticles at 20 μg/ml showed remarkable antimicrobial activity in vitro against the pathogen Acidovorax oryzae strain RS-2 of rice bacterial brown stripe, while 62.41% reduction in OD600 value was observed compared to the control. Moreover, the inhibitory efficiency of AgNPs increased with the increase of incubation time. Furthermore, AgNPs not only disturbed biofilm formation and swarming ability but also increased the secretion of effector Hcp in strain RS-2, resulting from damage to the cell membrane, which was substantiated by TEM images and live/dead cell staining result. Overall, this study suggested that AgNPs can be an attractive and eco-friendly candidate to control rice bacterial disease.